NLRP3 Inflammasome: A New Target for Prevention and Control of Osteoporosis? - Jiang, Na; An, Jinyang; Yang, Kuan; Liu, Jinjin; Guan, Conghui; Ma, Chengxu; Tang, Xulei (Frontiers in Endocrinology, 2021)
Abstract Osteoporosis is a systemic bone metabolism disease that often causes complications, such as fractures, and increases the risk of death. The nucleotide-binding oligomerization domain-like-receptor family pyrin domain-containing 3 (NLRP3) inflammasome is an intracellular multiprotein complex that regulates the maturation and secretion of Caspase-1 dependent proinflammatory cytokines interleukin (IL)-1β and IL-18, mediates inflammation, and induces pyroptosis. The chronic inflammatory microenvironment induced by aging or estrogen deficiency activates the NLRP3 inflammasome, promotes inflammatory factor production, and enhances the inflammatory response. We summarize the related research and demonstrates that the NLRP3 inflammasome plays a vital role in the pathogenesis of osteoporosis by affecting the differentiation of osteoblasts and osteoclasts. IL-1β and IL-18 can accelerate osteoclast differentiation by expanding inflammatory response, and can also inhibit the expression of osteogenic related proteins or transcription factors. In vivo and in vitro experiments showed that the overexpression of NLRP3 protein was closely related to aggravated bone resorption and osteogenesis deficiency. In addition, abnormal activation of NLRP3 inflammasome can not only produce inflammation, but also lead to pyroptosis and dysfunction of osteoblasts by upregulating the expression of Caspase-1 and gasdermin D (GSDMD). In conclusion, NLRP3 inflammasome overall not only accelerates bone resorption, but also inhibits bone formation, thus increasing the risk of osteoporosis. Thus, this review highlights the recent studies on the function of NLRP3 inflammasome in osteoporosis, provides information on new strategies for managing osteoporosis, and investigates the ideal therapeutic target to treat osteoporosis.